REPRESENTASI KEARIFAN LOKAL PADA NOVEL KENANGA KARYA OKA RUSMINI: KAJIAN ANTROPOLOGI SASTRA - Fakhry Lukmanul Hakiem; Odien Rosidin; Firman Hadiansyah (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to examine the representation of local wisdom in Balinese society as portrayed in the novel Kenanga by Oka Rusmini, using an anthropological literary approach and Roland Barthes' semiotic theory. The novel is rich in local cultural symbols, such as the caste system, traditional marriage customs, gender relations, and spiritual beliefs, all of which reflect the social structure of Balinese culture. To interpret the cultural meanings embedded within these symbols, this study applies Barthes’ theory of semiotics, which includes three levels of signification: denotation, connotation, and myth. The anthropological literary approach is used to understand the cultural context behind the text. This research employs a qualitative descriptive method with a close reading technique applied to textual excerpts that contain cultural signs. The data are analyzed through stages of sign identification, denotative description, connotative interpretation, and mythological reading, and further examined through the lens of Balinese local wisdom. The results of the study show that the cultural signs in Kenanga not only represent traditional values but also serve as a critique of the social system that restricts women's freedom. At the level of myth, it is found that ideologies such as caste hierarchy, honor, and female sacrifice are institutionalized through cultural language and symbols that appear natural. However, the characters in the novel also display forms of resistance against tradition, indicating that local wisdom is not static but can be negotiated in response to changing times.